Preparation method of polymer driver for improving bidirectional shape memory driving performance
By regulating the degree of cross-linking and semi-crystallization of polymer molecules, a three-dimensional network structure is formed, which solves the problems of self-drive reciprocating deformation, large drive strain, and complex shape changes in intelligent flexible drivers in a diversified environment, and achieves the improvement of bidirectional shape memory driving performance and rapid response capabilities.
Patent Information
- Application Number
- CN202411715471.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-25
AI Technical Summary
Intelligent flexible drivers achieve self-drive reciprocating deformation, large drive strain, and complex shape changes in a diversified environment, especially in narrow spaces or rough surfaces to perform actions such as peristaltic crawling, jumping, and reversible shrinking.
By regulating the degree of cross-linking and semi-crystallization of polymer molecules, peroxides are used to induce cross-linking reactions between free radicals and polymer main chains to form a three-dimensional network structure, thereby improving the bidirectional shape memory driving performance.
It has achieved improvements in the performance of bidirectional shape memory driving, enhanced driving resilience, promoted high-temperature gas heat transfer, achieved rapid response, and provided a soft and flexible deformation space for intelligent driving.
Smart Images

Figure CN119505346A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lightweight flexible actuators and intelligent polymer materials, and in particular to a method for preparing a polymer actuator capable of improving bidirectional shape memory driving performance. Background Art
[0002] Bidirectional shape memory materials undergo reversible changes in shape under external stimuli such as heat, light, humidity, and electricity. They can autonomously and reversibly transform between the original shape and the temporary shape without the need for external force to deform again. With the development of soft robots and intelligent actuators, research on reversible deformation materials has received more and more attention, so many scientists are committed to developing and exploring polymers with bidirectional shape memory behavior. However, the application scenarios of intelligent flexible actuators are becoming more and more diversified, requiring high driving strains to perform various complex deformation actions, such as crawling, jumping, and reversible contraction in narrow spaces or on rough surfaces. Whether self-driven reciprocating deformation, large driving strains, and transformation of complex shapes to adapt to diversified environments can be achieved has become the biggest challenge currently facing lightweight flexible actuators.
[0003] Bidirectional shape memory polymers with temperature-driven functions trigger the deformation of the polymer in the direction of external stress at low temperatures and shape recovery in the opposite direction at high temperatures due to the transition between the stationary phase and the reversible phase in the polymer network. The function of the stationary phase is to prevent flow deformation and restore the polymer from a temporary shape to its initial shape. It can be a stable network structure in the polymer such as a chemical cross-linked structure, molecular entanglement, and interpenetrating network structure; the reversible phase in the molecular network refers to a transformable structure. When the external stimulus changes, these transformable structures change and give the material the ability to deform. It can be a transformable structure such as crystal melting-recrystallization, rubber state-glass state, etc. Therefore, it is crucial to improve the polymer driving performance by studying and regulating the molecular network regions of the stationary phase and the reversible phase.
[0004] To solve the above problems, the present application proposes a method for preparing a polymer actuator with improved bidirectional shape memory driving performance. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a polymer actuator with improved bidirectional shape memory driving performance. By regulating the degree of molecular cross-linking and the degree of semi-crystallization, the improvement of the bidirectional shape memory driving performance and the reversible stability of the polymer are achieved, making a beneficial contribution to the application fields of lightweight flexible driving device materials in reciprocatingly deformable soft robots, retractable tissue scaffold implants, etc.
[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a polymer actuator for improving bidirectional shape memory driving performance, the specific steps are as follows: 1) Preparation of polyethylene vinyl acetate-sodium chloride particles-xylene-benzoyl peroxide mixture by solution polymerization 1.1) adding a quantitative amount of linear polyethylene vinyl acetate polymer having a flexible skeleton and ester-based small units into a xylene organic solvent, and sealing and stirring at high temperature until the polymer is dissolved to obtain a uniformly mixed polyethylene vinyl acetate polymer solution; 1.2) 10 wt% benzoyl peroxide and sodium chloride particles are added into the polyethylene vinyl acetate polymer solution in sequence, and stirred at a constant speed in an open state at a high temperature to obtain a viscous polyethylene vinyl acetate-sodium chloride particles-xylene-benzoyl peroxide mixed solution that is mixed and dispersed uniformly; 2) Preparation of polyethylene vinyl acetate-sodium chloride particles-benzoyl peroxide composite materials The mixed solution obtained in step 1.2) is poured into a polytetrafluoroethylene mold, placed in a vacuum oven for vacuum drying, and after the solvent is largely evaporated and the bubbles in the mixture are completely removed, the mixture is placed in an oven to remove the residual solvent, and then placed in a fume hood for 1 day to obtain a polyethylene vinyl acetate-sodium chloride particle-benzoyl peroxide composite material; 3) Peroxide heat induces free radical cross-linking reaction with polymer main chain 3.1) The blended composite material obtained in step 2) is coated with a "double layer", the inner layer is wrapped with Teflon tape, and then the outer layer is coated with a layer of aluminum foil, and finally the coated composite material is placed on a polytetrafluoroethylene plate and sent to a high-temperature vacuum tube furnace cavity; 3.2) The composite material is placed in a tube furnace and protected by nitrogen under vacuum to carry out a thermal crosslinking reaction between the free radicals initiated by peroxide and the main chain of the polymer. The thermal crosslinking reaction temperature is set at 200°C-350°C; 4) Preparation of bidirectional shape memory polymer actuators with different actuation properties Particle leaching was used to construct a porous structure. The polyethylene vinyl acetate-sodium chloride particle-benzoyl peroxide composite material after the reaction was immersed in distilled water, and the sodium chloride particles were dissolved and leached out to form an interconnected pore structure, thereby obtaining a bidirectional shape memory polymer actuator with different driving performances.
[0007] Preferably, in step 1.1), the dissolution conditions are high temperature 80°C with uniform magnetic stirring for 12 h, and the ratio of polyethylene vinyl acetate polymer to xylene organic solvent is 1:4; the molecular formula of the polyethylene vinyl acetate polymer is (CH2CH2) m [CH2CH(OCOCH3)] n, wherein the content of vinyl acetate is 18 wt %, and the average number average molecular weight of polyethylene vinyl acetate is 2000; and the density of the organic solvent xylene is 0.86 g / mL.
[0008] Preferably, in step 1.2), the mass percentage ratio of the polymer to dibenzoyl peroxide is 10:1; the molecular formula of the benzoyl peroxide is (C6H5CO)2O2, and its average number average molecular weight is 242.23; the mass percentage ratio of the polyethylene vinyl acetate polymer to the sodium chloride particles is 1:5, the sodium chloride particles are porogens, and the particle leaching porogen used may include one or more of sodium chloride, glucose and gelatin particles, and the particle size of the sodium chloride particles is 160-450 μm; high temperature 80°C magnetic stirring, the stirring time is 6 h.
[0009] Preferably, in step 2), a plastic film with tiny holes is wrapped around a polytetrafluoroethylene mold containing the mixed solution; the process of solvent volatilization and bubble removal is carried out in a vacuum oven at a temperature of 85°C for 12 hours; the oven temperature is 90°C for 24 hours.
[0010] Preferably, in step 3.2), the thermal cross-linking reaction temperature is 200°C, 250°C, 350°C, and the reaction time is 7 h; the nitrogen flow rate of the tubular furnace is 60 mL / min; after the thermal cross-linking reaction of the heat-initiated free radicals and the polymer main chain is completed, the composite material is placed in a vacuum tubular furnace filled with nitrogen and automatically cooled to room temperature.
[0011] Preferably, in step 4), the composite material is repeatedly immersed in 35° C. distilled water, the distilled water is changed 5-8 times, and the immersion time is 2-3 days.
[0012] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The present invention connects the benzene radicals generated by the peroxide initiator to the polymer main chain through a thermal crosslinking reaction to form a polymer molecular chain with a three-dimensional network structure. The thermal crosslinking reaction temperature is controlled to regulate the density of the three-dimensional network crosslinking structure to improve the driving performance of the bidirectional reversible shape memory porous polymer. Compared with controlling the initiator ratio, this method is simple, efficient, easy to regulate, and easy to functionalize. It has a significant effect on improving the bidirectional shape memory driving performance, and simultaneously realizes a stable reversible deformation cycle, providing ideas for the regulation of the crosslinking network of intelligent flexible driving polymer molecules in the future.
[0013] 2. The present invention integrates the bidirectional shape memory effect and the elastic soft body structure design in the same polymer system to construct a bidirectional shape memory porous polymer, which can not only realize the reversible bidirectional driving function of deformation, but also its three-dimensional anisotropic porous cavity can enhance the driving strain, promote the heat transfer of high-temperature gas to achieve rapid response, and provide a soft and flexible deformation space for intelligent driving, so that the polymer can self-contract, self-expand, twist, bend, spirally wind back and forth reversibly like sponges and boneless fleshy animals, and has the functions of high compressibility, dynamic osmotic response to stimulation, energy impact absorption, sound absorption and sound insulation, and easy structural regulation. In the field of soft robots in my country, there is great potential for cutting-edge applications such as deep space exploration, artificial muscles, biomedicine, smart wearables, and aerospace. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 A comparison diagram of the bidirectional shape memory driving performance cycle curves obtained at different thermal crosslinking temperatures of the present invention; Figure 2 Schematic diagram of programming the bidirectional shape memory reversible deformation function of the sample of the present invention. DETAILED DESCRIPTION
[0015] For a better understanding of the present invention, the following examples are further descriptions of the present invention.
[0016] The present invention adopts a design strategy of cross-linking polyethylene vinyl acetate semi-crystalline network polymer by heat-initiated benzoic acid free radicals, and systematically designs the molecular network structure by regulating the thermal cross-linking reaction temperature to improve the bidirectional shape memory driving performance, which has not been studied yet.
[0017] Embodiment 1: A method for preparing a polymer actuator for improving bidirectional shape memory driving performance, the specific steps are as follows: 1) Preparation of polyethylene vinyl acetate-sodium chloride particles-xylene-benzoyl peroxide mixture by solution polymerization 10 g of polyethylene vinyl acetate polymer was added to 40 mL of xylene organic solvent, and the mixture was sealed and stirred at a constant speed for 12 h at 80 °C until the polymer was dissolved. Then 1.11 g of benzoyl peroxide and 50 g of sodium chloride particles were added to the polyethylene vinyl acetate polymer solution in sequence, and the mixture was stirred at a constant speed for 6 h at 80 °C in a fume hood to obtain a mixed and dispersed viscous polyethylene vinyl acetate-sodium chloride particles-xylene-benzoyl peroxide mixture. 2) Preparation of polyethylene vinyl acetate-sodium chloride particles-benzoyl peroxide composite materials The prepared mixture of polyethylene vinyl acetate-sodium chloride particles-xylene-benzoyl peroxide was poured into a polytetrafluoroethylene mold, and the mold opening was sealed with a plastic film with tiny holes, and the mixture was placed in an 85 ℃ vacuum oven for 12 h to allow the solvent to evaporate slowly and remove bubbles, and then placed in a 90 ℃ oven for 24 h to remove the residual solvent, and finally placed in a fume hood for 1 day to obtain a polyethylene vinyl acetate-sodium chloride particles-benzoyl peroxide composite material; 3) Peroxide heat induces free radical cross-linking reaction with polymer main chain The prepared blended composite material was wrapped with Teflon tape and aluminum foil "double layer" and placed in a high-temperature vacuum tube furnace. Nitrogen was passed through the vacuum state to protect the thermal cross-linking reaction between the peroxide-induced free radicals and the polymer main chain. The thermal cross-linking reaction temperature was set to 200 ° C, the reaction time was 7 h, and the nitrogen flow rate was 60 mL / min. After the reaction was completed, the composite material was placed in a vacuum tube furnace with nitrogen and automatically cooled to room temperature.
[0018] 4) Preparation of bidirectional shape memory porous polymer soft actuators with different driving properties Particle leaching was used to construct a porous structure. The polyethylene vinyl acetate-sodium chloride particle-benzoyl peroxide composite material after the reaction was completed was immersed in 35 ℃ distilled water. The distilled water was changed 5-8 times and the immersion time was 2-3 days. The sodium chloride particles were dissolved and leached to form an interconnected pore structure, thus obtaining a bidirectional shape memory polymer actuator with different driving performances.
[0019] Embodiment 2: A method for preparing a polymer actuator for improving bidirectional shape memory driving performance, the specific steps are as follows: 1) Preparation of polyethylene vinyl acetate-sodium chloride particles-xylene-benzoyl peroxide mixture by solution polymerization 10 g of polyethylene vinyl acetate polymer was added to 40 mL of xylene organic solvent, and the mixture was sealed and stirred at a constant speed for 12 h at 80 °C until the polymer was dissolved. Then 1.11 g of benzoyl peroxide and 50 g of sodium chloride particles were added to the polyethylene vinyl acetate polymer solution in sequence, and the mixture was stirred at a constant speed for 6 h at 80 °C in a fume hood to obtain a mixed and dispersed viscous polyethylene vinyl acetate-sodium chloride particles-xylene-benzoyl peroxide mixture. 2) Preparation of polyethylene vinyl acetate-sodium chloride particles-benzoyl peroxide composite materials The prepared mixture of polyethylene vinyl acetate-sodium chloride particles-xylene-benzoyl peroxide was poured into a polytetrafluoroethylene mold, and the mold opening was sealed with a plastic film with tiny holes, and the mixture was placed in an 85 ℃ vacuum oven for 12 h to allow the solvent to evaporate slowly and remove bubbles, and then placed in a 90 ℃ oven for 24 h to remove the residual solvent, and finally placed in a fume hood for 1 day to obtain a polyethylene vinyl acetate-sodium chloride particles-benzoyl peroxide composite material; 3) Peroxide heat induces free radical cross-linking reaction with polymer main chain The prepared blended composite material was wrapped with Teflon tape and aluminum foil "double layer" and placed in a high-temperature vacuum tube furnace. Nitrogen was passed through the vacuum state to protect the thermal crosslinking reaction between the peroxide-induced free radicals and the polymer main chain. The thermal crosslinking reaction temperature was set to 250 ° C, the reaction time was 7 h, and the nitrogen flow rate was 60 mL / min. After the reaction was completed, the composite material was placed in a vacuum tube furnace with nitrogen and automatically cooled to room temperature.
[0020] 4) Preparation of bidirectional shape memory porous polymer soft actuators with different driving properties Particle leaching was used to construct a porous structure. The polyethylene vinyl acetate-sodium chloride particle-benzoyl peroxide composite material after the reaction was completed was immersed in 35 ℃ distilled water. The distilled water was changed 5-8 times and the immersion time was 2-3 days. The sodium chloride particles were dissolved and leached to form an interconnected pore structure, thus obtaining a bidirectional shape memory polymer actuator with different driving performances.
[0021] Embodiment 3: A method for preparing a polymer actuator for improving bidirectional shape memory driving performance, the specific steps are as follows: 1) Preparation of polyethylene vinyl acetate-sodium chloride particles-xylene-benzoyl peroxide mixture by solution polymerization 10 g of polyethylene vinyl acetate polymer was added to 40 mL of xylene organic solvent, and the mixture was sealed and stirred at a constant speed for 12 h at 80 °C until the polymer was dissolved. Then 1.11 g of benzoyl peroxide and 50 g of sodium chloride particles were added to the polyethylene vinyl acetate polymer solution in sequence, and the mixture was stirred at a constant speed for 6 h at 80 °C in a fume hood to obtain a viscous polyethylene vinyl acetate-sodium chloride particles-xylene-benzoyl peroxide mixed solution that was mixed and dispersed uniformly. 2) Preparation of polyethylene vinyl acetate-sodium chloride particles-benzoyl peroxide composite materials The prepared mixture of polyethylene vinyl acetate-sodium chloride particles-xylene-benzoyl peroxide was poured into a polytetrafluoroethylene mold, and the mold opening was sealed with a plastic film with tiny holes, and the mixture was placed in an 85 ℃ vacuum oven for 12 h to allow the solvent to evaporate slowly and remove bubbles, and then placed in a 90 ℃ oven for 24 h to remove the residual solvent, and finally placed in a fume hood for 1 day to obtain a polyethylene vinyl acetate-sodium chloride particles-benzoyl peroxide composite material; 3) Peroxide heat induces free radical cross-linking reaction with polymer main chain The prepared blended composite material was wrapped with Teflon tape and aluminum foil "double layer" and placed in a high-temperature vacuum tube furnace. Nitrogen was passed through the vacuum state to protect the thermal cross-linking reaction between the free radicals initiated by peroxide and the main chain of the polymer. The thermal cross-linking reaction temperature was set to 300 ° C, the reaction time was 7 h, and the nitrogen flow rate was 60 mL / min. After the reaction was completed, the composite material was placed in a vacuum tube furnace with nitrogen and automatically cooled to room temperature.
[0022] 4) Preparation of bidirectional shape memory porous polymer soft actuators with different driving properties Particle leaching was used to construct a porous structure. The polyethylene vinyl acetate-sodium chloride particle-benzoyl peroxide composite material after the reaction was completed was immersed in 35 ℃ distilled water. The distilled water was changed 5-8 times and the immersion time was 2-3 days. The sodium chloride particles were dissolved and leached to form an interconnected pore structure, thus obtaining a bidirectional shape memory porous polymer soft actuator with different driving performances.
[0023] The porous polymers of Examples 1-3 were cut into cylinders with a diameter of 4-9 mm and a thickness of 4-9 mm, and the temperature-driven bidirectional shape memory actuation performance was tested by thermomechanical analysis (TMA). Figure 1 , the schematic diagram of bidirectional shape memory reversible deformation function programming is as follows Figure 2 .
[0024] from Figure 1 It can be seen that different thermal crosslinking temperatures show different bidirectional shape memory actuation performances, and the bidirectional actuation strain increases with the increase of thermal crosslinking temperature, indicating that the actuation deformation is getting larger and larger, which is caused by the continuous increase of molecular network crosslinking density. From the above, it can be seen that the molecular crosslinking network and the crystalline melt-recrystallization phase as the providers of internal stress tension state are closely related to triggering bidirectional reversible actuation deformation (such as Figure 2 ).
[0025] In summary, the present invention uses a peroxide-initiated cross-linking strategy with benzoic acid free radicals and a semi-crystalline polymer main chain structure. By controlling the cross-linking reaction temperature, the polymer cross-linking density and the degree of semi-crystallization are regulated to achieve a high-driving-efficiency conversion of thermal energy to mechanical kinetic energy, thereby greatly improving the bidirectional shape memory driving strain and obtaining a flexible bidirectional shape memory actuator with excellent self-driven reciprocating deformation, large driving deformation, and complex shape change driving performance.
[0026] The above is only a preferred embodiment of the present invention. It should be noted that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications should also be considered as the protection scope of the present invention.
Claims
1. A method for preparing a polymer actuator for improving bidirectional shape memory driving performance, characterized in that it comprises the following steps: 1) Preparation of polyethylene vinyl acetate-sodium chloride particles-xylene-benzoyl peroxide mixture by solution polymerization 1).1 Add a quantitative amount of linear polyethylene vinyl acetate polymer having a flexible skeleton and ester-based small units into a xylene organic solvent, and stir in a sealed state at a high temperature until the polymer is dissolved to obtain a uniformly mixed polyethylene vinyl acetate polymer solution; 1).2 Add 10 wt% benzoyl peroxide and sodium chloride particles into the polyethylene vinyl acetate polymer solution in sequence, stir at a constant speed in an open state at a high temperature, and obtain a viscous polyethylene vinyl acetate-sodium chloride particle-xylene-benzoyl peroxide mixed solution that is mixed and dispersed uniformly; 2) Preparation of polyethylene vinyl acetate-sodium chloride particles-benzoyl peroxide composite materials The mixed solution obtained in step 1) and 2 is poured into a polytetrafluoroethylene mold, placed in a vacuum oven for vacuum drying, and after the solvent is largely evaporated and the bubbles in the mixture are completely removed, the mixture is placed in an oven to remove the residual solvent, and then placed in a fume hood for 1 day to obtain a polyethylene vinyl acetate-sodium chloride particle-benzoyl peroxide composite material; 3) Peroxide heat induces free radical cross-linking reaction with polymer main chain 3).1 Double-coat the blended composite material obtained in step 2), the inner layer is wrapped with Teflon tape, and then the outer layer is coated with a layer of aluminum foil, and finally the coated composite material is placed on a polytetrafluoroethylene plate and sent to a high-temperature vacuum tube furnace cavity; 3).2 The composite material is placed in a tube furnace and protected by nitrogen in a vacuum state to carry out a thermal crosslinking reaction between the free radicals initiated by peroxide and the main chain of the polymer. The thermal crosslinking reaction temperature is set to 200°C-350°C; 4) Preparation of bidirectional shape memory polymer actuators with different actuation properties Particle leaching was used to construct a porous structure. The polyethylene vinyl acetate-sodium chloride particle-benzoyl peroxide composite material after the reaction was immersed in distilled water, and the sodium chloride particles were dissolved and leached out to form an interconnected pore structure, thereby obtaining a bidirectional shape memory polymer actuator with different driving performances.
2. The method for preparing a polymer actuator for improving bidirectional shape memory driving performance according to claim 1, characterized in that: In step 1.1), the dissolution conditions are high temperature 80 ° C and uniform magnetic stirring for 12 h, the ratio of polyethylene vinyl acetate polymer to xylene organic solvent is 1:4; the molecular formula of the polyethylene vinyl acetate polymer is (CH2CH2) m [CH2CH(OCOCH3)] n , wherein the content of vinyl acetate is 18 wt %, and the average number average molecular weight of polyethylene vinyl acetate is 2000; and the density of the xylene organic solvent is 0.86 g / mL.
3. The method for preparing a polymer actuator for improving bidirectional shape memory driving performance according to claim 1, characterized in that: In step 1.2), the mass percentage ratio of polyethylene vinyl acetate polymer to dibenzoyl peroxide is 10:1; the molecular formula of the benzoyl peroxide is (C6H5CO)2O2, and its average number average molecular weight is 242.23; the mass percentage ratio of polyethylene vinyl acetate polymer to sodium chloride particles is 1:5, the sodium chloride particles are porogens, and the particle leaching porogens used include one or more of sodium chloride, glucose and gelatin particles, and the particle size of the sodium chloride particles is 160-450 μm; high temperature 80 ° C magnetic stirring, the stirring time is 6 h.
4. The method for preparing a polymer actuator for improving bidirectional shape memory driving performance according to claim 1, characterized in that: In step 2), a plastic film with small holes is wrapped around a polytetrafluoroethylene mold containing the mixed solution; the process of solvent volatilization and bubble removal is carried out in a vacuum oven at a temperature of 85°C for 12 h; the oven temperature is 90°C for 24 h.
5. The method for preparing a polymer actuator for improving bidirectional shape memory driving performance according to claim 1, characterized in that: In step 3.2), the thermal cross-linking reaction time is 7 h; the nitrogen flow rate of the tubular furnace is 60 mL / min; after the thermal cross-linking reaction between the heat-initiated free radicals and the polymer main chain is completed, the composite material is placed in a vacuum tubular furnace filled with nitrogen and automatically cooled to room temperature.
6. The method for preparing a polymer actuator for improving bidirectional shape memory driving performance according to claim 1, characterized in that: In step 4), the composite material is repeatedly immersed in 35° C. distilled water, the distilled water is changed 5-8 times, and the immersion time is 2-3 days.
Citation Information
Cited By
Preparation method for improving driving performance of stimuli-responsive polymer film
CN121021886A